Makrozoobentos Sebagai Indikator Biologi Dari Kualitas Air Di Sungai Kumpeh Dan Danau Arang-Arang Kabupaten Muaro Jambi, Jambi - Asra, Revis (Biospecies, 2009)
This research is used for know the water quality in Kumpeh River and Arang-arang Lakein Kumpeh district based on macrozoobenthic as the biological indicator. To know the communitystructures of macrozoobenthic so it used the analysis of Diversity Index, which uses the Shannon –Weaner Diversity Index. Based on the result of these identification, it was found the quality ofmacrozoobenthic index diversity for Kumpeh River and Arang-arang Lake were between 1.0 - 1.5 andboth of them has been classified as the moderately polluted group. The index of macroozobenthicdiversity of Kumpeh River are about 1.21 and Arang-arang Lake about 1.19 and 1.33. The existencesof Indicator species like Chironomous sp., Scatella sp. And Branchiura sowerbyi are also indicate thatboth of water was polluted.